Treatment outcome of NSCLC patients with BRAFnon-V600E mutations: a retrospective, multicentre analysis within the national Network Genomic Medicine (nNGM) Lung Cancer in Germany - Kropf-Sanchen, Cornelia; Rasokat, A.; Christopoulos, Petros; Wenzel, C.; Wehler, T.; Rost, M.; Kulhavy, J.; Reinmuth, N.; Schulz, C.; Scheffler, M.; Wolf, J.; Büttner, R.; et al. (ESMO open, 2025)
Background - Non-small-cell lung cancer patients with BRAFV600E mutations benefit from targeted and (chemo-)immune therapy. However, treatment of BRAFnon-V600E mutations poses substantial challenges due to biological heterogeneity, different clinicogenomic features and limited therapy outcome data. - Materials and methods - We conducted a retrospective analysis of BRAFnon-V600E mutation patients in the national Network Genomic Medicine Lung Cancer, assessing treatment outcomes upon targeted and (chemo-)immune therapy. Additionally, we evaluated mitogen-activated protein kinase (MEK)/extracellular-signal-regulated kinase (ERK) activation potential of selected, previously not characterized mutations in vitro. - Results - Fifty-three patients with 11 different BRAFnon-V600E mutations undergoing targeted and/or (chemo-)immune therapy were identified. Patients with class I mutations achieved the longest progression-free survival (PFS) under targeted therapy [median PFS (mPFS) 9.8 months], whereas chemotherapy and chemoimmunotherapy led to an mPFS of 35 and 27 months, respectively. In patients with class II mutations, targeted therapy led to an mPFS of 6.3 months while chemotherapy, chemoimmunotherapy and immunotherapy resulted in an mPFS of 3.5, 3.7 and 3.6 months, respectively. Preclinical characterization demonstrated MEK phosphorylation potential and hence actionability of BRAF class II mutations G469A, G469R, G469V and BRAF K601. Patients exhibiting class III mutations did not respond to targeted therapy (mPFS 2.6 months), but showed responses to chemotherapy (mPFS 4.2 months), chemoimmunotherapy (mPFS 10.9 months) and immunotherapy (mPFS 7 months). - Conclusions - Patients with activating BRAFnon-V600E mutations respond to BRAF/MEK inhibitor or (chemo-)immunotherapy, while those with non-activating mutations do not benefit from targeted therapy, but may benefit from (chemo-)immune therapy. Correlating preclinical activation assays with clinical outcomes can guide treatment decisions for patients with BRAFnon-V600E mutations, facilitating personalized treatment approaches.
Im Titel ist "non-V600E" hochgestellt
Online verfügbar: 14. Juli 2025, Artikelversion: 14. Juli 2025
Gesehen am 19.08.2025